Da identidade à abjeção: Sexualidade, Inteligibilidade & Violência em Judith Butler - CHAVES, Gustavo José de Sousa (2022)
This research supported by the criticism of the philosopher Judith Butler (1956), has the main topic of investigation as: is it possible to resignify the construction of human intelligibility, from an epistemic criticism of sexual assumptions, which were developed by modern occidental epistemologies (structuralists and psychoanalytic)? This research has a qualitative and exploratory approach made through a review of literature. It was methodologically developed with theoretical analysis, deconstructivist theory, and hermeneutics interpretation. To answer this guiding question, the analysis contemplates three interpretative issues: first, to present the ways that gender standards impose their own regulations, which presuppose and reaffirm heterosexual norms as the only way of intelligible access of culture and identity; the second issue is to specify how that system of regulation operates as an act of power historically and socially created, sanctioned and rightfully incorporated to modern epistemologies and, thus, creating a social intelligible field of humans, while it excludes people with diverse sex-genders. Concurrently, that system of sex-gender regulation impress, at psycological level, the internalization of a desire sanctioned by homosexual repudiation; the third issue highlights how that way of access to identity and culture turns the socio psychological acknowledgement of people in disagreement with symbolic standards of intelligibillity as unfeasible and compelling. Another goal is to present the way that the author proposes a theory of subjectivity that problematizes and open spaces for the creation of identities that resist the essentialist concepts of sex-gender-desire and its sexual practices. Lastly, the inextricable relation between identity and abjection in the fight for acknowledgement is put in evidence. Indulging the impossibility of a humanistic project, nowadays, that does not include the difference (différance) as constitutive to identities, under the risk of failing in the construction of an ethics of life that can be lived.